Merchants in Early Byzantine Hagiographic Texts - Milewski, Ireneusz (Studia Ceranea, 2024)
This article deals with accounts devoted to merchants and merchant activity that can be found in hagiographic texts from the early Byzantine era. Such accounts are few and far between, which is surprising, especially when compared to the patristic texts of the time. The accounts pertain both to rich merchants and to small “retail” vendors whom the merchants employed to distribute the imported goods or to sell them at market fairs. As shown by the cases dealt with in this article, merchants ran a serious risk of losing their merchandise, which could either be stolen (the case described by Theodoret of Cyrus) or destroyed as a result of naval disasters (cases described by Leontios of Neapolis).